THE INFLUENCE OF BANKS SPECIFIC FACTORS, MACRO ECONOMIC FACTORS, AND INDUSTRIAL FACTORS ON NON-PERFORMING FINACING OF SHARIA BANKS IN INDONESIA FOR THE 2013–2022 PERIOD - Muhammad Yahya; Abdurrahman Abdurrahman (JURNAL ILMIAH EDUNOMIKA, 2024)
Indonesia, as a country with the largest Muslim population, requires special attention to sharia banks because these financial institutions can be an alternative that allows people to avoid the practice of usury, which is contrary to sharia financial principles. Through sharia banks, people can access financial services that are in accordance with their religious beliefs. However, this sector faces various types of risks that not only affect its financial well-being, but also endanger the stability of the entire country and are one of the risks of bank financing. Financing problems are a major challenge to the stability of the banking sector. For this reason, this research aims to identify the factors that influence NPF in Islamic commercial banks in Indonesia. on 10 banks listed on the Indonesia Stock Exchange for the 2013-2022 period, and using data analysis methods by applying panel data regression techniques. The research results show that Bank Size, Financing Growth, Bank Diversification, Bank Competition and Inflation have no effect on NPF. On the other hand, Bank Operational Inefficiency, FDR, Bank Profitability, and CAR affect NPF.